The Improving of English Literacy For Group of Children In Desa Kayu Jati Use Monkey Stories Aplicatio - Khairunnisah Khairunnisah; Aprilia Enjelika Munthe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research is an idea to overcome the problems faced by a group of children in Kayu Jati Village, Panyabungan, Mandailing Natal. The purpose of this research is to build the English literacy motivation of the children's group to gain knowledge and implement it by speaking English and reading English texts. The core of English literacy in this study is digital literacy or the use of media or Monkey Stories application as a source of reading and introduction to vocabulary and other activities available in the application.Monkey Stories application is a complete application that teaches children to listen, speak, read and write in English and is intended for children 2-10 years old. The learning methods provided by 'Monkey Stories' address most of these issues. All the audio in the app is recorded by native speakers and rated by leading language experts. So the group of children can easily understand the English words and follow the instructions explained in the app. With an attractive and illustrated display, it certainly helps in fostering children's interest in English literacy.Key word : Literacy, English, Group of Children, Monkey Stories